Pengembangan Keterampilan Membuat Puisi Melalui Permainan Tradisional ABC 5 Dasar Pada Siswa SMA Kelas 10 - Falah Arifbillah Subagiyo; Rendis Eka Arisandi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
improving poetry-writing skills among 10th-grade students. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. In the first cycle, 60% of students actively participated, with an average score of 70 on their poetry tests. After revisions and improvements in the second cycle, student participation increased to 85%, and the average test score rose to 85, reflecting a 21.4% improvement. Data were collected through observations, interviews, written tests, and documentation. The findings indicate that the